Comparison of the Effectiveness of Group Schema Therapy and Mindfulness-Based Stress Reduction on Psychological Symptoms and Resilience in Individuals Seeking Divorce - Hasanpour Asil , Bahareh; Zarbakhsh Bahri, Mohammadreza; HamzehPoor Haghighi, Tahereh (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to compare the effectiveness of group schema therapy and mindfulness-based stress reduction (MBSR) on psychological symptoms and resilience in individuals seeking divorce. The research method was a quasi-experimental design with a pre-test, post-test, and a control group, along with a three-month follow-up period. The statistical population included individuals seeking divorce who referred to Family Court Complex No. 2 in Velenjak, Tehran, between December 2023 and March 2024, totaling 501 individuals. A sample of 60 eligible participants was selected based on inclusion and exclusion criteria using convenience sampling and was randomly assigned to two experimental groups and one control group (each group consisting of 20 individuals). The data collection instruments included the Depression, Anxiety, and Stress Scale (DASS) (Lovibond & Lovibond, 1995) and the Connor-Davidson Resilience Scale (CD-RISC) (Connor & Davidson, 2003). All three groups underwent a pre-test using the research instruments. Then, group schema therapy and MBSR interventions were separately administered to their respective experimental groups over eight 90-minute sessions, while the control group was placed on a waitlist. Upon completion of the interventions, a post-test was conducted for both experimental and control groups, followed by a follow-up test three months later. The data were analyzed using repeated-measures analysis of covariance (ANCOVA). The findings indicated that both group schema therapy and MBSR significantly impacted psychological symptoms and resilience in individuals seeking divorce (p < .05). The results of the Scheffé test demonstrated a statistically significant difference in the effectiveness of the two interventions on psychological symptoms (p < .05; MD = 2.50), with MBSR being more effective than group schema therapy in reducing psychological symptoms. However, there was no statistically significant difference between the two interventions regarding resilience enhancement (p > .05; MD = 2.97), suggesting that both therapies equally contributed to increasing resilience. The effects remained stable at the three-month follow-up. This study suggests that group schema therapy and MBSR can significantly help reduce psychological disorders such as stress, anxiety, and depression while enhancing resilience in individuals undergoing divorce.